A apropriação do livro didático do PNLD pelo professor de Português - Ricardo Souza Netto (2021)
This research originated from a survey carried out with undergraduate students from the supervised internships of analysis and practice at the Faculty of Languages of the Federal University of Minas Gerais (FALE/UFMG). The results and self-perceptions obtained during these internships signaled a certain distancing of public school teachers in Belo Horizonte in relation to the use of the adopted Portuguese textbook (LDP) in the classroom. This observation gave rise to the conviction of the need to investigate the LDP in order to understand the materiality of this phenomenon and its circumstances. Thus, the present work intends to map the use of the LDP, to answer the fundamental question: How is the textbook appropriated by public school teachers of Elementary (6th to 9th grade) and High School in Belo Horizonte? In this way, a documental and bibliographic investigation was carried out to understand the evolution of the textbook in the country and the conceptions that gave rise to the current LDP. The theoretical foundation is based on: Choppin's (2020c p. 21) classification, which establishes the textbook as “the book that serves to teach”; and in the enunciative-discursive perspective of the language used in the orientation of the curricula, through the Common National Curriculum Base (BNCC), and in the elaboration of the LDP, as a result of the National Textbook Program (PNLD) notices. The survey of comparative results of Brazilian students in “reading” in the International Student Assessment Program (PISA) pointed to the possibility of verifying another theoretical possibility, which was done through a succinct analysis of extracts from the English curriculum. Methodologically, a field survey was also carried out with a survey, using an unidentified structured questionnaire as instrument that was answered online by a sample of 42 Portuguese teachers, from Elementary School (6th to 9th grade) and High School, from public schools in Belo Horizonte. The data obtained, analyzed and interpreted quantitatively and qualitatively, confirmed the partial use of the LDP by teachers, caused mainly by reasons arising from the structure and content of the LDP, and also by aspects related to the teachers' own training, the characteristics of the students and the perspective enunciative-discursive that guides the elaboration of the LDP and the BNCC. In addition to these conclusions, it was also verified the convenience of carrying out further studies – to deepen and detail the findings of this work – which may contribute to a better understanding of the scenario of Portuguese Language teaching in the country.